"I Know How to Manage My Time": Refusal Strategies by EFL Nursing Students. (April 2022) - Mohammad, Abeer
Health professionals who come from different cultural backgrounds are required to interact competently and at the most acceptable communication level that meets the demands of the multicultural context in which English is the medium of communication. Lack of proper communication in such contexts can establish a hostile work environment. Thus, health programs should prepare students interactionally to operate within the work environment competently. A total of 42 nursing students in a Saudi university responded to a Discourse Completion Test. The data show that nursing students demonstrate a tendency to use direct refusal strategies, especially when refusing a request. The analysis also reveals problematic refusal semantic formulas used to address a higher-status person. Thus, diagnosing such communication issues can contribute to establishing a healthy work environment.